Enhancing Student Learning Outcomes in The Qur'an Interpretation Course Through The Implementation of The Start From Reading (SFR) Cooperative Learning Model - Karman, Karman; Maslani, Maslani; Anwar, Rosihon; Yudhiantara, Rully Agung; Djubaedi, Djubaedi (Nazhruna: Jurnal Pendidikan Islam, 2024)
Conventional teaching methods have been noted to stifle student creativity potentially. In contrast, Cooperative learning, characterized by group-based activities, fosters an interactive and communicative learning atmosphere. Embracing the principles of Cooperative learning, the Start from Reading (SfR) model can be applied to Quranic studies in Islamic higher education institutions. This study assessed the efficacy of the SfR learning model in improving student learning outcomes in the Qur'an interpretation course at the Arabic Language Education Studi Program (ALESP), UIN Sunan Gunung Djati Bandung. Employing a quasi-experimental design, the research analyzed pre-test and post-test scores from experimental and control groups. Findings revealed a significant increase in post-test scores, rising from an average of 70.00 in pre-tests to 77.15, highlighting the effectiveness of the SfR model in enhancing student learning. These outcomes emphasize the importance of incorporating the SfR model into Quranic education, potentially enriching student learning experiences and achievements in this academic domain.